IoT-Based Integrated Marketing Communication in Closing Quality Agent Marketing Program - Nova Jelita Desilia Ajeng; Endy Gunanto Marsasi (Jurnal Informatika Ekonomi Bisnis, 2023)
The researcher examines a digital economy-based manufacturing industry company where the company has a Closing Quality Agent program that aims to screen the network below, namely screening Closing Quality Agent program that aims to filter the network under it, namely screening qualified and serious agents in running this business. The applicable Closing Quality Agent will have an impact on the entire network if the agent does not pass the qualification. This research was conducted to try to help and evaluate existing programs in the company The method for analyzing this research is qualitative by direct observation, in-depth interviews, collection of documentation, and secondary data of the company. Research is carried out in the company through the marketing division. Based on research that has been carried out, this program is less effective in maximizing its digital system. This research resulted in a program evaluation using the theory of Integrategrated Marketing Communication with the implementation of the Internet of Things which is expected to be implemented in the company system in supporting the Closing Quality Agent program is carried out.